Tsenguluso ya vhuumba na vhungonwa kha luambo na matshilisano a Tshivenda - Nekhongoni, Manthageli Edward (University of Limpopo, 2013)
The study examines the impact of sterility on Tshivenḓa language and social life. The study deals with words and other linguistic aspects that are generated by this condition and how sterility influences social relations among the Vhavenḓa.
Thesis (M.A. ( African languages)) --University of Limpopo, 2013
Keywords: Sterility; Tshivenda Language; 496.963976; Language and Languages; Venda language